2016
DOI: 10.3233/jad-160461
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Amyloid-β and Axonal Degeneration Pathology in Delirium

Abstract: The reduction in CSF Aβ42, indicating β-amyloidosis, and increase in T-tau, indicating neurodegeneration, in hip fracture patients without dementia developing delirium indicates that preclinical AD brain pathology is clinically relevant and possibly plays a role in delirium pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 504 publications
4
63
3
Order By: Relevance
“…Dementia is one of the strongest risk factors for delirium (Ahmed et al, ; Fong et al, ). However, of the three studies that examined whether levels of established CSF markers for dementia were associated with risk of delirium only Idland et al showed a convincing relationship (Idland et al, ). These findings may be related to the presence of incipient dementia, and future studies should take this into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dementia is one of the strongest risk factors for delirium (Ahmed et al, ; Fong et al, ). However, of the three studies that examined whether levels of established CSF markers for dementia were associated with risk of delirium only Idland et al showed a convincing relationship (Idland et al, ). These findings may be related to the presence of incipient dementia, and future studies should take this into account.…”
Section: Discussionmentioning
confidence: 99%
“…Idland et al () also studied hip fracture patients. They found that, in patients without dementia, delirium was associated with lower CSF Aβ42 levels and higher t‐tau levels and lower ratios of Aβ42 to t‐tau and p‐tau.…”
Section: Risk Markers Of Deliriummentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have associated the “CSF-AD signature” described above with delirium. Patients with post-operative delirium have a reduced CSF Aβ42/Tau ratio 15 and a recent study 16 found patients without dementia who developed delirium had lower CSF Aβ42 levels, higher T-tau levels, and lower ratios of Aβ42 to T-tau and P-tau relative to those without delirium. In contrast, other studies did not find significant differences between preoperative CSF Abeta1β42, tau, and P-tau levels in participants who did and did not develop delirium 17 .…”
Section: Ad Biomarkers and Deliriummentioning
confidence: 92%
“…In individuals without dementia, some studies have reported an association between cerebrospinal fluid (CSF) or plasma levels of Aβ and tau and delirium (Idland et al, 2016; van den Boogaard et al, 2011; Xie et al, 2014) while others have not (Witlox et al, 2011). Similarly, some magnetic resonance imaging (MRI) studies of regional brain volume and delirium have identified an association (Gunther et al, 2012; Shioiri et al, 2016) while others have not (Cavallari et al, 2015; Root et al, 2013).…”
Section: Introductionmentioning
confidence: 99%